A Fast and Simple Contact Printing Approach to Generate 2D Protein Nanopatterns - Lindner, Marco; Tresztenyak, Aliz; Fülöp, Gergö; Jahr, Wiebke; Prinz, Adrian; Prinz, Iris; Danzl, Johann G.; Schütz, Gerhard J.; Sevcsik, Eva (Frontiers in Chemistry, 2019)
Protein micropatterning has become an important tool for many biomedical applications as well as in academic research. Current techniques that allow to reduce the feature size of patterns below 1 µm are, however, often costly and require sophisticated equipment. We present here a straightforward and convenient method to generate highly condensed nanopatterns of proteins without the need for clean room facilities or expensive equipment. Our approach is based on nanocontact printing and allows to fabricate protein patterns with feature sizes of 80 nm and periodicities down to 140 nm. This was made possible by the use of the material X poly(dimethylsiloxane) (X-PDMS) in a two-layer stamp layout for protein printing. In a proof of principle, different proteins at various scales were printed and the pattern quality was evaluated by atomic force microscopy and super-resolution fluorescence microscopy.